Impact response of thick glass fibre reinforced polyester laminates - Zhou, G.; Davies, G.A.O. (International journal of impact engineering, 1995)
Thick glass/polyester woven roving laminated plates subject to low-velocity impact have been investigated using a guided drop-weight test rig in ascending energy order up to 1500 J. The impact response and energy-absorbing characteristics have been determined by impact-forces and absorbed-energy histories, and by force-displacement relationships. Impact damage is examined by visual inspection, ultrasonic C-scan and an optical microscope so that a three-staged sequential damage model is proposed to characterize damage growth. Static tests are also conducted to examine strain rate effect. It is demonstrated that the maximum impact forces are increased by 36% for the thin plates and by 22% for the thick plates, although the initial threshold forces are less strain-rate sensitive. Two thicknesses of laminated plates are used to study the thickness effect, and the scaling rules are developed for the delaminated plates. It is shown that both the maximum static and impact forces, and the incident kinetic energy can be scaled by the thickness ratio if these laminates have the same diameter and their behaviour is dominated by shear. The finite element modelling is carried out for relatively low energy cases, the impact structural response is well captured by linear elastic solution.